The Effect of Flood Disaster Preparendness Education on Public Knowledge In Perigi Vilage Pulau Pinang Sub District, Lahat District In 2020 - Kamesyworo Kamesyworo; Eka Haryanti (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Natural disasters can occur suddenly or through a process that takes place slowly. The occurrence of flood disasters is greatly influenced by natural factors in the form of rainfall that is above normal and the presence of rising tides. Disaster preparedness is a condition of a community that is both physically and psychologically sound in facing a disaster. The purpose of this study was to determine the effect of flood disaster preparedness education on public knowledge of Perigi Village, Pulau Pinang District, Lahat Regency. The research method used is a quassy experimental method with one group pretest-posttest design design. The study population was all families (communities) in Perigi Village, Pulau Pinang District, Lahat Regency. The sampling technique is incidental sampling. Data were collected from respondents by distributing questionnaires before and after counseling to respondents.